APPLICATION OF THE A* METHOD IN MAKING COURSE SCHEDULING DECISIONS AT STMIK MULIA DARMA - Panjaitan, Muhammad Iqbal; Rajagukguk, Denni M; Manalu, Mamed Rofendi; Sihombing, Monang Juanda Tua; Siregar, Kristian (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
One of the biggest issues in managing higher education is course scheduling, where a variety of criteria need to be taken into account in a balanced way, including lecturer availability, classroom size, and student preferences. This procedure can be greatly optimized by using the A* method, also referred to as the optimal path finding algorithm. Applying the A* technique to course scheduling decisions is the goal of this research, which attempts to improve efficiency and happiness for all stakeholders.A customized A* algorithm is designed and implemented as part of the research process to manage scheduling characteristics such lecturer schedule compatibility, space allocation, and time slots. We tested this technique on scheduling data from an Indonesian university. The results of the tests indicate that the A* approach can yield a more optimal.